2021
DOI: 10.1007/s13593-021-00699-8
|View full text |Cite
|
Sign up to set email alerts
|

A superweed in the making: adaptations of Parthenium hysterophorus to a changing climate. A review

Abstract: Parthenium weed (Parthenium hysterophorus L.) is a globally invasive plant with significant negative impacts on the environment, agriculture, economy, and health. This invasion problem is likely to be exacerbated by climate change. Elevated atmospheric carbon dioxide concentration ([CO 2 ]), high ambient temperatures, heatwaves, and droughts will facilitate the establishment, range expansion, and interference potential of this invasive species while making its management more difficult. Here, for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…They reported that climate change favors the expansion, growth and multiplication of wheat pests. Furthermore, climate change opens new geographic windows for weed infestations (Mao et al, 2021;Vilà et al, 2021), insect biodiversity (Raven & Wagner, 2021) and disease outbreaks (Chaloner et al, 2021) across Fig. 6 Interactive effect of elevated CO 2 , temperature, and drought on soil organic carbon the globe.…”
Section: Overview Of Responses To Biotic Stressesmentioning
confidence: 99%
“…They reported that climate change favors the expansion, growth and multiplication of wheat pests. Furthermore, climate change opens new geographic windows for weed infestations (Mao et al, 2021;Vilà et al, 2021), insect biodiversity (Raven & Wagner, 2021) and disease outbreaks (Chaloner et al, 2021) across Fig. 6 Interactive effect of elevated CO 2 , temperature, and drought on soil organic carbon the globe.…”
Section: Overview Of Responses To Biotic Stressesmentioning
confidence: 99%
“…Parthenium weed (Parthenium hysterophorus L.) belongs to the family Asteraceae and is one of the most invasive plant species with an ever-expanding introduced range around the world [14]. It is an aggressive, herbaceous weed with multiple morphological and physiological characteristics making it highly adaptable to various biotic and abiotic stresses [14][15][16]. Massive infestations are often observed on vacant land, disturbed sites, roadsides, railway track sides, and wastelands [15].…”
Section: Introductionmentioning
confidence: 99%
“…Massive infestations are often observed on vacant land, disturbed sites, roadsides, railway track sides, and wastelands [15]. Parthenium weed invades and causes significant production losses in many major field crops, including wheat (Triticum aestivum L.), rice (Oryza sativa L.), sorghum [Sorghum bicolor (L.) Moench], maize (Zea mays L.), and sugarcane (Sachharum officinarum L.) in over 40 countries in Asia-Pacific and Africa [14,15,17]. The weed is also a major production constraint in grazing lands, pastures and livestock systems in many parts of the world [15,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations